BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN PENGARUHNYA TERHADAP KINERJA KARYAWAN PT. KRAKATAU SARANA PROPERTI CILEGON – BANTEN - Fatari, Fatari; Sabrawijaya, Sabrawijaya; Sumarsih, Rani Sri; Noberta, Nicky (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The purpose of this study was to determine the effect of organisational culture and leadership style both partially and simultaneously (together) on the performance of employees of PT Krakatau Sarana Properti. The research method uses quantitative methods, with data collection techniques through questionnaires. The sampling technique uses saturated sampling method with a sample size of 40 respondents.  Based on the results of the t test (partial) the organisational culture variable (X1) obtained a t value greater than the t table (5,448 > 2,024) with a significance value smaller than 5% (0,000 < 0,05) while the results of the t test of the leadership style variable (X2) obtained the value of t is greater than t table (7,153 > 2,024) with a significance value smaller than 5% (0,000 < 0,05). As well as the results of the F test, the calculated F value is greater than the F table (49,868 > 3,25) with a significance value smaller than 5% (0,000 < 0,05). It can be concluded that organisational culture and leadership style both partially and simultaneously have a positive and significant effect on the performance of employees of PT Krakatau Sarana Properti